Cerebriform intradermal nevus - A rare clinical entity presenting as cutis verticis gyrata - Chandramohan Kudligi; Vidya Kuntoji; Pradeep Vittal Bhagwat; Chovatiya Keyur Mohanbhai; Safura Tazeen (Our Dermatology Online, 2017)
Cutis verticis gyrata is a rare skin condition characterized by convoluted folds and furrows formed from thickened skin resembling a cerebriform pattern. The condition is usually but not exclusively limited to the scalp. It may present in either primary form with or without any associations or in secondary forms with a wide variety of causes. Cerebriform intradermal nevus is one such rare cause of this unusual condition. We present a case of cerebriform intradermal nevus involving scalp and the upper half of left cheek which had both cerebriform appearances as well as the smooth surface.